The Development of Indonesia As The Rule of Law Based On 1945 Constitution Before And After Amendments - Bambang Panji Gunawan; Surti Yustianti; Mohammad Roesli; Bastianto Nugroho (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
Prior to amendment of the 1945 Constitution, constitutional basis of Indonesia that Indonesia is a state based on law is contained in the preamble of the 1945 Constitution body. Statement that Indonesia is a country of law is also mentioned in the 1945 Constitution explanation. Article 1 (3) of the 1945 Constitution states that "Indonesia is a state of law". The provisions of the aforementioned article constitute the constitutional basis that Indonesia is a state that implements a constitutional system in accordance with the elements of the legal state; law is placed as the only rule in the life of society, nation and state (supremacy of law). There is different meaning between Indonesia is a state based on law and Indonesia is a state law.Applicability of the 1945 before and after the amendment is followed by different constitutional structure, which will give different meaning as a state based on law.Continental European legal systems recognized rechtsstaat legal state while other parts of the world recognize concept of rule of law state extracted from anglosaxon states. Both laws state models prioritize different aspects. Rechtsstaat concept prioritizes wetmatigheid principles which later becomes rechtmatigheid, meanwhile the rule of law prioritize equality before the law. Due to differences in emphasis in these operations, there arose the different elements between rechtsstaat concept and rule of law concept.